Pengaruh Media Sosial dalam Membentuk Identitas Kewarganegaraan yang berakar pada Nilai-Nilai Pancasila - Sri Yunita; Ayu Tri Chahyani; Hanaya Manuela Ambarita; Iwidya Risti Sinaga; Nabila Devia Hummaira (Journal on Education, 2024)
In the era of globalization and the rapid development of information technology, social media has become a phenomenon that influences various aspects of life, especially for the younger generation. This discussion examines the impact of social media use on individuals and national identity, especially in the context of Pancasila values as the identity of the Indonesian nation. In the analysis, it was revealed that social media plays an important role in shaping social relationships, communication, self-identity and individual mental health. However, unwise use of social media can threaten the understanding and application of Pancasila values, with the potential to damage the existence of the nation's ideology. The younger generation, as the hope of the nation, is influenced by trends and lifestyles on social media, often adopting foreign cultures that conflict with national identity. It is necessary to use social media wisely, be aware of its limitations, and build a realistic self-image to maintain the integrity of Pancasila values as the foundation of a just and civilized social life. The Influence of Social Media in Forming a Citizenship Identity Rooted in Pancasila Values. Pancasila must become a lifestyle for the younger generation. It is important to continue to support Pancasila education among the younger generation and monitor the use of social media so that Pancasila remains a strong guide for the country's future. By understanding the influence of social media in forming a civic identity rooted in Pancasila values, it is hoped that this research can provide better knowledge about social and political dynamics in the current digital era, as well as contribute to the development of a more inclusive and sustainable society. The research method used in this research is a qualitative method with a descriptive approach.